Self-draining bipolar plate: Experimentation with various catalyst-loading in a low temperature proton exchange membrane fuel cell - Sudesh Bekal; Shripad T Revankar (AIMS Energy)
The paper presents the results of experimental studies on a self-draining bipolar plate used in a low-temperature polymer electrolyte membrane fuel cell (L-PEMFC). These studies investigated the cell's performance under varying platinum catalyst loadings and different hydrogen and oxygen flow rates.Two catalyst loading configurations were tested: (ⅰ) 0.20 mg/cm2 (anode) and 0.40 mg/cm2 (cathode) and (ⅱ) 0.25 mg/cm2 (anode) and 0.50 mg/cm2 (cathode). The gas diffusion layer (GDL) employed was carbon paper, with the catalyst arranged on the carbon substrate.Hydrogen flow rates of 80,100, and 120 ml/min were assessed alongside oxygen supplies at 50%, 100%, and 150% excess relative to the stoichiometric requirement (0%) in relation to the hydrogen supply for both catalyst loading conditions. Additional experiments were conducted at humidification temperatures of 60, 70, 80, 90, and 100 ℃, using the optimal hydrogen flow rate and oxygen supply conditions. To evaluate the stability, the fuel cell operated continuously for 5 hours at the optimal humidification temperature to assess the stability of voltage and power output.The fuel cell using the self-draining bipolar plate demonstrated an approximately 30% increase in load-bearing capacity. However, it did not show significant differences in voltage or power across the varying catalyst loadings. The optimal humidification temperature was determined to be 90 ℃. This study provides valuable insights into the continuous operation of fuel cells under optimal conditions of humidification, excess oxygen, and hydrogen flow rate.